Private choices, public costs: Evaluating cost-shifting between private and public health sectors in New Zealand. Issue 3 (March 2021) - Penno, Erin; Sullivan, Trudy; Barson, Dave; Gauld, Robin
Highlights: Boundaries between NZ's public and private health sectors are not well defined. Two percent of private admissions had a public readmission within 7 days. The cost of public hospital admissions related to private events was NZ11.5 million. A third of subsequent admissions related to complications of a medical procedure. Understanding the drivers of cost-shifting is important in dual health systems. Abstract: New Zealand's dual public-private health system allows individuals to purchase health services from the private sector rather than relying solely upon publicly-funded services. However, financial boundaries between the public and private sectors are not well defined and patients receiving privately-funded care may subsequently seek follow-up care within the public health system, in effect shifting costs to the public sector. This study evaluates this phenomenon, examining whether cost-shifting between the private and public hospital systems is a significant issue in New Zealand. We used inpatient discharge data from 2013/14 to identify private events with a subsequent admission to a public hospital within seven days of discharge. We examined the frequency of subsequent public admissions, the demographic and clinical characteristics of the patients and estimated the direct costs of inpatient care incurred by the public health system. Approximately 2% of private inpatient events had a subsequent admission to a public hospital. Overall, the costs to the public system amounted to NZ11.5 million, with a median cost of NZ2800. At least a third of subsequent admissions were related to complications of a medical procedure. Although only a small proportion of private events had a subsequent public admission, the public health system incurred significant costs, highlighting the need for greater understanding and discussion around the interface between the public and private health systems.